2020
DOI: 10.3390/ani10101744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Andrographolide Levels on Growth Performance, Antioxidant Capacity, Intestinal Immune Function and Microbioma of Rice Field Eel (Monopterus Albus)

Abstract: An eight-week feeding trial was conducted to investigate the effects of dietary andrographolide on the growth performance, antioxidant capacity in the liver, intestinal inflammatory response and microbiota of Monopterus albus. A total of 900 health fish (25.00 ± 0.15 g) were randomly divided into five groups: AD1 (the basal diet) as the control, and AD2, AD3, AD4 and AD5 groups, which were fed the basal diet supplemented with 75, 150, 225 and 300 mg/kg andrographolide, respectively. The results showed that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 69 publications
3
17
1
Order By: Relevance
“…Antioxidant enzyme activity is regulated by the nrf2/keap1 signaling pathway [ 54 ]. keap1 inhibits the expression of antioxidant genes by inhibiting the nuclear translocation of nrf2 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant enzyme activity is regulated by the nrf2/keap1 signaling pathway [ 54 ]. keap1 inhibits the expression of antioxidant genes by inhibiting the nuclear translocation of nrf2 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important component of the intestinal physical barrier is tight junction protein. Studies have reported that tight junction proteins are closely related to the integrity of intestinal structure, and the upregulation of transmembrane protein-related genes (including occluding , zo-1, and zo-2 ) can maintain the structural integrity of intestinal epithelial cells, while the upregulation of cytoplasmic protein-related genes (including claudin-12 and claudin-15 ) can damage the structural integrity of intestinal epithelial cells [ 54 , 72 ]. This present study found that oxidized-fish-oil diets substantially downregulated intestinal zo-1 and zo-2 mRNA transcriptional levels of channel catfish, and upregulated claudin-12 and claudin-15 mRNA transcriptional levels, indicating that oxidized-fish-oil diets may increase the intestinal barrier structure damage caused by intercellular space by regulating tight junction protein genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of experimental feeds were configured: control group (basal feed) and andrographolide group (basal feed + 150 mg/kg andrographolide) (Table 1). According to the results of our previous study, the optimal concentration of andrographolide was 150 mg/kg (Shi, Zhong, et al, 2020). The andrographolide was provided by Hunan Jiaruisi Biological Technology.…”
Section: Methodsmentioning
confidence: 98%
“…Traditional Chinese medicine ( TCM ) has been regarded as an invaluable source of therapeutic agents and played an important role in maintaining both human and animal health ( Mishra and Tiwari, 2011 ). Some TCMs with low toxicity, like Galla Chinensis ( Xiang et al., 2015 ), Andrographis paniculata ( Worasuttayangkurn et al., 2019 ), Arctii Fructus ( Xu et al., 2015 ; Bok et al., 2017 ), Glycyrrhizae Radix ( Jiang et al., 2020a ), and Schizonepeta tenuifolia ( Fung and Lau, 2002 ), contain various active ingredients, such as terpenoids, phenols, and volatile oils, which can not only improve growth performance, immune function, and intestinal microbiota of livestock and poultry, but also have antioxidant and anti-inflammatory activities ( Samuel et al., 2017 ; Li et al., 2018 ; Pirgozliev et al., 2019 ; Jiang et al., 2020b ; Shi et al., 2020 ). Compared with antibiotics, TCMs have many advantages including less toxicity and side effects, and reduced residues in body and risk of inducing drug resistance ( Abdallah et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%